Clinical and Demographic Profile of Patients with Crohn's Disease in Specialized Hospital for Gastrointestinal and Liver Diseases and Surgery in Al-Najaf Province - AL-Kefaei , Ghadaq Hameed Neamah (Medical Science Journal for Advance Research, 2024)
Background: Crohn’s disease (CD) It is a chronic inflammation that occurs in the digestive system. This disease is widespread in developing countries. Aim of study: To estimation the ratio of clinical and demographic data of CD patients at Specialized Hospital for Gastrointestinal and Liver Diseases and Surgery in AL- Najaf Province. Patients and Methods : Demographic and clinical data were obtained by medical analysis data to patients attended into Specialized Hospital for Gastrointestinal and Liver Diseases and Surgery in AL- Najaf Province from October 2022 to March 2024. Results: Sixty-four patients diagnosed with Crohn's disease participated in this study. The findings indicated that the majority of individuals infected with this disease were women, with the age group of 30 to 39 years being the most prevalent among the infected population. The findings indicate that freelancers and housewives are the most impacted by this disease. The results indicated that the majority of patients visiting the hospital are from Najaf Governorate. The disease was diagnosed through biopsy samples collected from different regions of the digestive system, and the treatment for the majority of patients involved immunosuppressant medications. Conclusions: Despite the increasing incidence, we highlight the Education and a extra intestinal manifestation in this study, and reflecting a high need for hospitalization and immune-modulatory, and uses biological treatment, , and surgery.